Insulation

By using aluminoxic acid ceramic materials with low thermal conductivity and true space separation structure, the shortcomings of traditional high thermal conductivity ceramic materials under the demand for high thermal insulation are solved, and efficient thermal insulation effect is achieved.

JP7649211B2Active Publication Date: 2025-03-19KYOCERA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021116610
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-14
Publication Date
2025-03-19
Estimated Expiration
2041-07-14

AI Technical Summary

Technical Problem

Traditional high-pressure discharge lamps made of transparent aluminooxyacid ceramic materials with high thermal conductivity do not have sufficient insulation properties in applications where high thermal insulation requires.

Method used

The columnar body and substrate made of aluminoxo acid ceramic material with low thermal conductivity are formed in a vacuum state in the internal space and arranged the columnar body therebetween. The tip of the column body is closely connected with the grooves of the substrate but maintains a slight gap to improve insulation performance.

Benefits of technology

By using low thermal conductivity ceramic materials and true space isolation structures, the thermal insulation performance of the insulator is significantly improved and is suitable for applications where high thermal insulation is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649211000001
    Figure 0007649211000001
  • Figure 0007649211000002
    Figure 0007649211000002
  • Figure 0007649211000003
    Figure 0007649211000003
Patent Text Reader

Abstract

To provide a fitting body with high thermal insulation and a connecting mechanism having the fitting body.SOLUTION: A first fitting body of the present disclosure includes a columnar body comprising a first ceramic composed mainly of aluminum oxide at least at a tip, and a substrate comprising a second ceramic composed mainly of aluminum oxide having a recess into which the tip is inserted. The tip is fitted into the recess and has a gap between the tip surface of the tip and the inner bottom surface of the recess.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a fitting body. Insulation having Regarding. [Background technology]

[0002] Conventionally, shrink fitting has been used to fit ceramics together. For example, Patent Document 1 proposes a high-pressure discharge lamp in which end caps made of translucent alumina are hermetically joined to both ends of a cylindrical container body made of translucent alumina by shrink fitting, forming a discharge space inside. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP2006-93046A Summary of the Invention [Problem to be solved by the invention]

[0004] The high pressure discharge lamp proposed in Patent Document 1 is formed by shrink fitting without gaps using translucent alumina, a ceramic with high thermal conductivity. Translucent alumina is made of crystal grains with large diameters, and the proportion of grain boundary phases that hinder thermal conduction is small. In addition, because the translucent alumina is shrink fitted without gaps, the thermal conduction at the fitting portion between the translucent alumina pieces is good. Therefore, there is a problem that the fitting body of translucent alumina is not suitable for applications that require high thermal insulation.

[0005] The object of the present disclosure is to provide a fitting having high thermal insulation properties. Insulation with The purpose of this project is to provide [Means for solving the problem]

[0006] The first aspect of the present disclosure to solve the above problems is Insulation teeth, The device comprises a base and a lid placed on the top surface of the base, and an internal space for maintaining a vacuum state is formed between the base and the lid, and a plurality of pillars are disposed at predetermined intervals within the internal space.At least the tip portion is made of a first ceramic mainly composed of aluminum oxide. the law of nature , The substrate is A second ceramic mainly made of aluminum oxide having a recess into which the tip portion is inserted. do. The tip portion is fitted into the recess, and there is a gap between a tip surface of the tip portion and an inner bottom surface of the recess.

[0007] The second aspect of the present disclosure Insulation teeth, The device comprises a base and a lid placed on the top surface of the base, an internal space for maintaining a vacuum state is formed between the base and the lid, and a plurality of pillars are disposed at predetermined intervals within the internal space. The ceramic substrate has a protruding portion made of a first ceramic material mainly composed of aluminum oxide and a base portion supporting the protruding portion. death , The substrate is A second ceramic mainly made of aluminum oxide having a recess into which the protrusion is inserted. Lana The protrusion is fitted into the recess, and a gap is formed between a tip surface of the protrusion and an inner bottom surface of the recess. Effect of the Invention

[0009] The first aspect of the present disclosure Insulation In this case, both the columnar body and the base are formed from ceramics mainly composed of aluminum oxide, which has low thermal conductivity, and the tip of the columnar body is fitted into a recess in the base, with a gap between the tip face of the tip and the inner bottom surface of the recess, thereby improving thermal insulation. The second aspect of the present disclosure Insulation In the present invention, the first and second members are both formed from ceramics whose main component is aluminum oxide, which has low thermal conductivity, and the convex portion of the first member is fitted into the concave portion of the second member, with a gap being formed between the tip surface of the convex portion and the inner bottom surface of the concave portion, thereby improving thermal insulation. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view of an insulation body having a fitting according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a partially enlarged cross-sectional view of FIG. [Diagram 3]3 is an enlarged cross-sectional view of the fitting body shown in FIG. 2. [Figure 4] FIG. 13 is a cross-sectional view of an insulator according to another embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, according to one embodiment of the present disclosure Insulation Fig. 1 shows a plate-shaped thermal insulator 1 having fittings according to one embodiment of the present disclosure.

[0012] 2, this thermal insulator 1 comprises a base 2 having a rising portion 21 on its periphery, and a lid 3 disposed on the upper surface of the base 2. The lower peripheral edge of the lid 3 is bonded to the upper surface of the rising portion 21 of the base 2 via a first bonding layer 4, and an internal space 5 is formed between the base 2 and the lid 3. The inside of the internal space 5 is maintained in a vacuum state by vacuum heating treatment or the like, thereby imparting high thermal insulation properties to the thermal insulator 1.

[0013] In the thermal insulator 1, a plurality of pillars 6 are arranged at predetermined intervals in the internal space 5 so as to be able to withstand reduced pressure. The pillars 6 are interposed between the base 2 and the lid 3, and serve to maintain a certain gap between the base 2 and the lid 3. The internal space 5 functions as a heat insulating layer. The width W of the internal space 5 is preferably 10 mm or more and 60 mm or less. The thicknesses of the base body 2 and the lid body 3 are preferably 10 mm or more and 30 mm or less, respectively.

[0014] FIG. 3 shows an example of a fitting body in which a columnar body 6 is fitted into a recess 7. As shown in FIG. 3, a recess 7 is formed on the inner surface of the cover body 3, and the tip of the columnar body 6 is inserted into this recess 7. The columnar body 6 is fitted into the recess 7, and the insulator 1 has a gap 8 between the tip surface of the columnar body 6 and the inner bottom surface of the recess 7. This improves the thermal insulation. The width w of the gap 8 at the axis of the recess 7 is preferably 0.03 mm or more. This increases the space occupied by the gap 8, further improving the thermal insulation. It is more preferable that the width w is 1 / 2 or less of the depth of the recess 7. If the width w is 1 / 2 or less of the depth of the recess 7, the tip of the columnar body 6 inserted into the recess 7 can be fitted and fixed, and can sufficiently withstand vibration and pulling force. On the other hand, the rear end of the column 6 is bonded to the inner surface of the lid 3 via a second bonding layer 9 .

[0015] In the present disclosure, at least the tip of the columnar body 6 is made of a first ceramic mainly composed of aluminum oxide, and the base body 2 is made of a second ceramic mainly composed of aluminum oxide. The first ceramic and the second ceramic both have a thermal conductivity of 33 W / (m K) or less, and preferably 32 W / (m K) or less at 20° C. In this way, since the tips of the columns 6 and the base 2 are both made of ceramics with low thermal conductivity, heat insulation is ensured. The thermal conductivity may be determined in accordance with JIS R 1611:2010.

[0016] The first ceramic forming the tip of the columnar body 6 preferably contains more aluminum oxide than the second ceramic of the base 2. This results in a smaller amount of glass component (sintering aid) in the first ceramic than in the second ceramic, improving mechanical properties such as three-point bending strength and rigidity of the tip of the columnar body 6. On the other hand, glass components are more likely to dissolve from the inner peripheral surface of the recess 7 facing the outer peripheral surface of the tip of the columnar body 6 during firing, which will be described later, improving the fitting strength and preventing the gap 8 from being blocked even when external pressure is applied from the rear end side of the columnar body 6. Here, the content of aluminum oxide in the second ceramic is 95 mass % or more, and preferably 96 mass % or more and 99 mass % or less.

[0017] The first ceramic and the second ceramic may contain aluminum oxide as a main component, and may also contain silicon, magnesium, and calcium. Specifically, the silicon may be contained in an amount of 0.01% by mass or more and 1% by mass or less in terms of oxide. The magnesium may be contained in an amount of 0.1% by mass or more and 0.4% by mass or less in terms of oxide. The calcium may be contained in an amount of 0.01% by mass or more and 1% by mass or less in terms of oxide. The total content of silicon, magnesium, and calcium elements converted into oxides is preferably smaller in the first ceramic than in the second ceramic. This increases the high-temperature creep property of the first ceramic, so that the tip of the columnar body 6 can be used in a high-temperature environment for a long period of time even if it is elongated. In particular, the difference in the total content of the above elements converted into oxides is preferably 0.6% by mass or more and 1% by mass or less.

[0018] The total content of silicon, magnesium, and calcium in the second ceramics calculated as oxides is preferably 1 mass % or less, which can increase the rigidity of the base 2 made of the first and second ceramics. Here, the total content of the above elements in the first ceramic calculated as oxides is, for example, 0.17 mass % or more and 0.57 mass % or less. The main components of the first and second ceramics refer to components that account for 90% or more by mass out of 100% by mass of the components that make up each ceramic, and each component may be identified by an X-ray diffraction apparatus using CuKα radiation. The content of the identified components may be calculated by calculating the content of elements using an ICP (Inductively Coupled Plasma) emission spectrometer or an X-ray fluorescence analyzer (XRF) and converting it into the identified components.

[0019] The first ceramic preferably has a smaller average circle-equivalent diameter of the aluminum oxide crystal grains than the second ceramic. This increases the mechanical properties of the tip, such as three-point bending strength and rigidity, and allows the tip and the protruding portion, which will be described later, to be longer. The circle-equivalent diameter can be determined according to the following procedure. First, the cross sections of the tip portions of the base body 2 and the columnar body 6 are polished to a mirror finish. Specifically, the following first to third polishings are carried out in this order. (1) First polishing: average particle size D 50 Polishing with a diamond disk using diamond abrasive grains with a diameter of 45 μm (2) Second polishing: average particle size D 50 Polishing with a copper plate using diamond abrasives with a diameter of 3 μm (3) Third polishing: average particle size D 50 Polishing with tin plate using diamond abrasive grains with a diameter of 0.5 μm The polished surface obtained by the above method is heat-treated at 1350°C, and the surface obtained is photographed at a magnification of 400 times using a digital macroscope (VHX-500). Specifically, the area of ​​the photographed image is 7.2 × 10 -3 mm 2 The measurement range is the range of the circle equivalent diameter of the aluminum oxide crystal particles. The measurement range is analyzed using image analysis software (e.g., WinROOF, manufactured by Mitani Shoji Co., Ltd.) to obtain the circle equivalent diameter of the aluminum oxide crystal particles. In the analysis, the threshold value of the circle equivalent diameter is set to 0.2 μm, and circle equivalent diameters of 0.2 μm or less are not included in the calculation of the average value.

[0020] The average circle-equivalent diameters of the first ceramic and the second ceramic determined by this measurement method are both smaller than the average circle-equivalent diameter (31.6 μm to 53.6 μm) of translucent alumina (e.g., LUCALOX, a trademark of General Electric Co.). For example, the average circle-equivalent diameter of the first ceramic is 3 μm or more and 8 μm or less, and the average circle-equivalent diameter of the first ceramic is 10 μm or more and 30 μm or less. And, both the first ceramic and the second ceramic do not transmit visible light, and have a relative density of 96% or more. The relative density of the first ceramic is the percentage of the apparent density with respect to the theoretical density of the first ceramic, and the apparent density is determined in accordance with JIS R 1634:1998. The relative density of the second ceramic can also be determined by the same method.

[0021] Next, a method for manufacturing the thermal insulator 1 will be described. First, the process of producing the base body 2 will be described. Aluminum oxide powder (with a purity of 99.9% by mass or more), which is the main component of the second ceramic, and powders of silicon oxide, magnesium hydroxide, and calcium carbonate are charged into a grinding mill together with a solvent (ion-exchanged water), and the average particle size (D 50 After pulverizing the powder to a particle size of 1.5 μm or less, an organic binder and a dispersant for dispersing the aluminum oxide powder are added and mixed to obtain a slurry.

[0022] Here, the content of silicon oxide powder is 0.01 to 0.05 mass%, the content of magnesium hydroxide powder is 0.15 to 0.57 mass%, the content of calcium carbonate powder is 0.9 to 1.8 mass%, and the remainder is aluminum oxide powder and unavoidable impurities, based on 100 mass% of the total of the above powders.

[0023] The organic binder is an acrylic emulsion, polyvinyl alcohol, polyethylene glycol, polyethylene oxide, or the like.

[0024] Next, the slurry is sprayed and granulated to obtain granules, and the granules are then filled into a mold. Using a uniaxial press molding device or a cold isostatic pressurizing device, the granules filled into the mold are pressed at a molding pressure of 78 MPa to 128 MPa to obtain a rectangular plate-shaped molded body. Then, by cutting, a depression that will become the recess 7 after firing and a surrounding space that will become the internal space 5 after the lid 3 is joined are formed in the molded body 1. The surrounding space is a space that opens on one side in the thickness direction of the molded body and is surrounded on the outer edge. A carbon sheet (not shown) is laid on the inner bottom surface of the depression. The thickness of the carbon sheet may be the same as the width w of the gap 8 to be formed. In consideration of degreasing properties, the carbon sheet is preferably porous, and in particular, the porosity is preferably 30% to 80%.

[0025] On the other hand, the molded body of the columnar body 6 is obtained in the same manner as the substrate 2. In this case, the content of silicon oxide powder is 0.3 to 1 mass %, the content of magnesium hydroxide powder is 0.15 to 0.57 mass %, the content of calcium carbonate powder is 0.018 to 0.9 mass %, and the remainder is aluminum oxide powder and unavoidable impurities, relative to a total of 100 mass % of the raw material powders constituting the molded body of the columnar body 6.

[0026] The produced molded columnar body 6 is fired to obtain a sintered body. The firing atmosphere is air, reduced pressure, or vacuum, the firing temperature is preferably 1500°C to 1700°C, and the holding time is preferably 4 hours to 6 hours. With the tip of the sintered columnar body 6 inserted into the recess, the rectangular plate-shaped molded body is fired under the same firing conditions as those described above. As a result, the tip of the columnar body 6 is fitted into the recess 7 due to firing shrinkage, and the carbon sheet disappears, forming a gap 8 between the tip surface of the columnar body 6 and the inner bottom surface of the recess 7.

[0027] Next, the lid 3 is attached. If the lid 3 is made of ceramics (for example, ceramics whose main component is aluminum oxide like the base 2), glass paste is applied to the other end face of the columnar body 6 and to the end face of the rising portion 21 located on the periphery of the base 2 to form a glass bond, thereby obtaining the insulator 1.

[0028] On the other hand, when the lid 3 is made of metal (e.g., stainless steel such as SUS304 or SUS630, aluminum, etc.), the other end face of the columnar body 6 and the end face of the rising portion 21 located on the periphery of the base 2 are respectively coated with brazing material (e.g., 63 to 70.5 mass% Ag-27.5 to 35 mass% Cu-2 mass% Ti) and brazed to obtain the insulator 1.

[0029] Next, according to another embodiment of the present disclosure, Insulation This will be explained based on Fig. 4. Insulation 1 The same components are denoted by the same reference numerals and the description thereof will be omitted. In this embodiment, the protrusion 11b and the base 11a supporting the protrusion 11b are provided. Column 11 ( First member ) and a recess 17 into which the protrusion 11b is inserted. Base 12( Second member ) The protrusion 11b is fitted into the recess 17, and a gap 8 is formed between the tip surface of the protrusion 11b and the inner bottom surface of the recess 17.

[0030] columnar body As with the columnar body 6 described above, at least the protruding portion 11b of the columnar body 11 is made of a first ceramic material mainly composed of aluminum oxide. base body Like the base 2 described above, 12 is made of a second ceramic containing aluminum oxide as a main component. The protrusion 11b can be formed by, for example, cutting.

[0031] The thermal insulator 1 produced using the fitting shown in Fig. 3 or 4 can be used in, for example, semiconductor manufacturing equipment, plasma equipment, etc., but is not limited to these uses. Also, the fitting shown in Fig. 3 or 4 can be used not only for the thermal insulator 1, but also for various uses that require fitting.

[0032] Although the embodiments of the present disclosure have been described above, the present disclosure is not limited to the above-described embodiments, and various modifications and improvements are possible within the scope of the present disclosure. [Explanation of symbols]

[0033] 1. Insulation 2 Base 21 Rising section 3 Lid 4 1st bonding layer 5. Interior Space 7 Recess 8 Gap 9 Second bonding layer 11 Columnar body ( First member ) 11a base 11b Convex part 12 Base ( Second member ) 17 Recess

Claims

1. A substrate; A lid body disposed on an upper surface of the base body, An internal space for maintaining a vacuum state is formed between the base body and the lid body, A thermal insulator having a plurality of pillars arranged at predetermined intervals in the internal space, At least a tip portion of the columnar body is made of a first ceramic mainly composed of aluminum oxide, the base is made of a second ceramic containing aluminum oxide as a main component and having a recess into which the tip portion is inserted; The tip portion is fitted into the recess, and a gap is provided between a tip surface of the tip portion and an inner bottom surface of the recess.

2. A substrate; A lid body disposed on an upper surface of the base body, An internal space for maintaining a vacuum state is formed between the base body and the lid body, A thermal insulator having a plurality of pillars arranged at predetermined intervals within the internal space, The columnar body has a protrusion made of a first ceramic containing aluminum oxide as a main component and a base supporting the protrusion, the base body is made of a second ceramic containing aluminum oxide as a main component and having a recess into which the protrusion is inserted; The convex portion is fitted into the concave portion, and a gap is provided between a tip surface of the convex portion and an inner bottom surface of the concave portion.

3. The heat insulator according to claim 1 or 2, wherein the width of the gap at the axis of the recess is 0.03 mm or more.

4. The heat insulator according to any one of claims 1 to 3, wherein the first ceramic has a higher aluminum oxide content than the second ceramic.

5. The heat insulator according to claim 4 , wherein the content of aluminum oxide contained in the second ceramic is 95 mass % or more.

6. The insulator according to any one of claims 1 to 5, wherein the first ceramic and the second ceramic contain silicon, magnesium and calcium, and the total content of these elements converted into oxides of the first ceramic is less than that of the second ceramic.

7. The heat insulator according to claim 6 , wherein the total content of silicon, magnesium and calcium contained in the second ceramics calculated as oxides is 1 mass % or less.

8. 8. The heat insulator according to claim 1, wherein the first ceramic has a smaller average equivalent circle diameter of aluminum oxide crystal grains than the second ceramic.

9. The heat insulator according to any one of claims 1 to 8, wherein the gap has a width w that is equal to or less than 1 / 2 the depth of the recess.

10. The heat insulator according to any one of claims 1 to 9, wherein the internal space has a width W of 10 mm or more and 60 mm or less.

Citation Information

Patent Citations

  • Joined structure of ceramic raw materials

    JP1999130554A

  • High-pressure discharge lamp

    JP2006093046A

  • Ceramic structure and manufacturing method thereof

    JP2020007175A